Buoyant flow of CO_2 through and around a semi-permeable layer of finite extent. (15th November 2016) - Ngo, Tri Dat; Mouche, Emmanuel; Audigane, Pascal
Abstract : The buoyancy- and capillary-driven counter-current flow of CO_2 and brine through and around a semi-permeable layer is studied both numerically and theoretically. The continuities of the capillary pressure and the total flux at the interface between the permeable matrix and layer control the CO_2 saturation discontinuity at the interface and the balance between the buoyant and capillary diffusion fluxes on each side of the interface. This interface process is first studied in a one-dimensional (1-D) vertical column geometry using the concept of extended capillary pressure and a graphical representation of the continuity conditions in the ( S_L, S_U ) plane, where S_L and S_U are the lower and upper saturation traces at the interface, respectively. In two dimensions, we heuristically extend the two-phase gravity current model to the case where the current is bounded by a semi-permeable layer. Consequently, the current is not saturated with CO_2, and its saturation and shape are derived from the flux and capillary pressure continuity conditions at the interface. This simplified model, which depends on CO_2 saturation only, is compared to fine grid simulations in the capillary-free and gravity-dominant cases. A good agreement is obtained in the second case; the current geometrical characteristics are accurately described. In the capillary-free case, we demonstrate that the local total velocity, which is, on average, zero because the flow is counter-current, must be considered in the total flux at the interface to obtain the same level of agreement.